Clinical outcomes of 1PN- and 3PN-derived blastocysts in the absence of transferable 2PN embryos: A retrospective analysis - Nuri Peker; Ayşen Yücetürk; Esra Tığlı; Özge Karaosmaoğlu; Burak Elmas; İlke Özer Aslan; Bülent Tıraş (PLOS One, 2026)
Objective We aimed to determine the blastocyst formation rates, preimplantation genetic testing for aneuploidy (PGT-A) results, and pregnancy rates of embryos derived from 1pronucleus (1PN) and 3 pronuclei (3PN). Methods A total of 150 patients who developed 1PN and/or 3PN embryos were enrolled in the study. The embryos were divided into three groups according to the number of pronuclei: group (i) consisted of 1PN embryos; group (ii) consisted of 3PN embryos; and group (iii) was the control group, which included 2PN embryos. The primary outcomes were the blastocyst formation rate and euploidy rate of the 1PN and 3PN embryos. The secondary outcomes were pregnancy and live birth rates after embryo transfer. Results A total of 1711 (72.1%) metaphase II (MII) oocytes were obtained among 2373 oocytes. A total of 508 day-5 embryos developed, of which 44 (8.7%) were identified as 3PN, 13 (2.6%) as 1PN, and 451 (88.8%) as 2PN. PGT-A was performed on 23 3PN embryos and 4 1PN embryos. Overall comparison revealed a significant difference among groups (chi-square (χ²) = 51.11, df = 2, p < 0.0001). In pairwise analyses, 1PN zygotes had significantly lower blastocyst formation rates than both 2PN and 3PN zygotes (both p < 0.0001), whereas the difference between 2PN and 3PN zygotes was not significant (p = 0.5025). All tested blastocysts were reported as aneuploid and none of these embryos were transferred. A total of five 3PN blastocyst transfers were performed in five patients, one 1PN blastocyst transfer was performed in one patient, and combined 1PN and 3PN blastocyst transfer was performed in one patient. Importantly, no preimplantation genetic testing for aneuploidy (PGT-A) was performed on the embryos selected for transfer, and all transfers were carried out without genetic testing. The only pregnancy was achieved in the patient who underwent combined transfer of 1PN and 3PN blastocysts. Conclusion Blastocyst formation and pregnancy rates derived from abnormally fertilized embryos are low; however, transfer of blastocysts derived from 1PN and 3PN embryos may be considered in patients who do not develop transferable 2PN blastocysts.